External Stimuli-Responsive Characteristics of Poly(N,N′-diethylacrylamide) Hydrogels: Effect of Double Network Structure - Julie Šťastná; Vladislav Ivaniuzhenkov; Lenka Hanyková (Gels, 2022)
Swelling experiments and NMR spectroscopy were combined to study effect of various stimuli on the behavior of hydrogels with a single- and double-network (DN) structure composed of poly(N,N′-diethylacrylamide) and polyacrylamide (PAAm). The sensitivity to stimuli in the DN hydrogel was found to be significantly affected by the introduction of the second component and the formation of the double network. The interpenetrating structure in the DN hydrogel causes the units of the component, which is insensitive to the given stimulus in the form of the single network (SN) hydrogel, to be partially formed as globular structures in DN hydrogel. Due to the hydrophilic PAAm groups, temperature- and salt-induced changes in the deswelling of the DN hydrogel are less intensive and gradual compared to those of the SN hydrogel. The swelling ratio of the DN hydrogel shows a significant decrease in the dependence on the acetone content in acetone–water mixtures. A certain portion of the solvent molecules bound in the globular structures was established from the measurements of the 1H NMR spin–spin relaxation times T2 for the studied DN hydrogel. The time-dependent deswelling and reswelling kinetics showed a two-step profile, corresponding to the solvent molecules being released and absorbed during two processes with different characteristic times.